Golden Jubilee of the Ghana Medical Journal - Ofori-Adjei, D. (Ghana medical journal, 2012)
Ghana Medical Association (GMA), was first released in September 1962. The Patron of the GMA at the time, Osagyefo Dr Kwame Nkrumah, the first President of the Republic of Ghana in congratulating the GMA wrote, “ The Ghana Medical Journal will afford the means of disseminating medical knowledge among yourselves and your colleagues throughout Africa and beyond. Your observations, analysis, management and discoveries in the problems of Health in Africa, and in Ghana in particular, will be making important contributions to man’s quest for good health. I am sure your journal will reflect the path Ghana has trodden in its vigorous attempt to ensure positive health for her people.”.
Journal Article
Keywords: Medical Journal; Ghana; Health